Vegetated Buffer Strips Can Lead to Increased Release of Phosphorus to Waters: A Biogeochemical Assessment of the Mechanisms - Stutter, Marc I; Langan, Simon J; Lumsdon, David G (Environmental science & technology, 2009)
Establishing vegetated buffer strips (VBS) between cropland and watercourses is currently promoted as a principal control of diffuse pollution transport. However, we lack the mechanistic understanding to evaluate P retention in VBS and predict risks of P transport to aquatic ecosystems. We observed that VBS establishment led to enhanced rates of soil P cycling, increasing soil P solubility and the potential amount leached to watercourses. Soil in VBS, relative to adjacent fields, had increased inorganic P solubility indices, dissolved organic P, phosphatase enzyme activity, microbial diversity, and biomass P. Small relative increases in the pool of soil P rendered labile had disproportionate effects on the P available for leaching. We propose a mechanism whereby the establishment of VBS on previous agricultural land causes a diversifying plant−microbial system which can access previous immobilized soil P from past fertilization or trapped sediment P. Laboratory experiments suggested that sediment-P inputs to VBS were insufficient alone to increase P solubility without biological cycling. Results show that VBS management may require strategies, for example, harvesting vegetation, to offset biochemical processes that can increase the susceptibility of VBS soil P to move to adjoining streams.